A compact dual‐polarized omnidirectional slot antenna for WiFi dual‐band applications. Issue 10 (30th June 2022) - Guo, Jingli; Guo, Dingzhang; Feng, Andi; Sun, Baohua; Sun, Qiao
Abstract: A compact dual‐polarized omnidirectional (DPO) antenna with dual‐band characteristic is presented in this article. The main structure of the antenna is a metal box, which is composed of a horizontally folded narrower slot on the three sides for vertical polarization and a vertically folded wider slot lying on other three sides for horizontal polarization. Two different coupling feedings inside the box are designed for the two slots so as to obtain good omnidirectional radiation properties in two frequency bands of 2.4 and 5.5 GHz. The proposed structure is only 30 mm × 30 mm × 10 mm in size (0.24λ0  × 0.24λ0  × 0.08λ0, λ0 stands for the wavelength of corresponding lowest operating frequency). A prototype has been built and measured. The measured results present the proposed dual‐band DPO antenna has two 10 dB return loss operating bandwidth of 3.7% (2.41–2.5 GHz) and 16% (5.05–5.93 GHz), with the isolation higher than 35 dB.